In vitro Liver Zonation of Primary Rat Hepatocytes - Tomlinson, Lauren; Hyndman, Lauren; Firman, James W.; Bentley, Robert; Kyffin, Jonathan A.; Webb, Steven D.; McGinty, Sean; Sharma, Parveen (Frontiers in Bioengineering and Biotechnology, 2019)
The ability of the liver to simultaneously carry out multiple functions is dependent on the metabolic heterogeneity of hepatocytes spatially located within a liver lobule spanning from the portal triad to the central vein. This complex zonal architecture of the liver, however, makes accurate in vitro modelling a challenge and often standard culture systems assume a homogenous model which may lead to inaccurate translatability of results. Here, we use a combination of mathematical modelling and experimental data to demonstrate a readily constructible in vitro flow system capable of liver zonation in primary rat hepatocytes. We show the differential expression of zonation markers, enhanced functionality when compared to standard static cultures and zone specific metabolism and cell damage in the presence of paracetamol, a known zone specific toxin. This type of advanced system provides a more in-depth and essential understanding of liver physiology and pathophysiology as well as the accurate evaluation of pharmacological interventions at a zone-specific level.